Uce-based phylogeny and classification of Megachilini - Christophe J. Praz; Morgan Gueuning; Michael G. Branstetter; Achik Dorchin; Terry Griswold; Laurence Packer; Stephan Risch; Jessica Litman (Molecular Phylogenetics and Evolution, 2026)

Ultraconserved yet informative for species delimitation: Ultraconserved elements resolve long‐standing systematic enigma in Central European bees - Morgan Gueuning; Juerg E. Frey; Christophe Praz (Molecular Ecology, 2020)
Accurate and testable species hypotheses are essential for measuring, surveying and managing biodiversity. Taxonomists often rely on mitochondrial DNA barcoding to complement morphological species delimitations. Although COI‐barcoding has largely proven successful in assisting identifications for most animal taxa, there are nevertheless numerous cases where mitochondrial barcodes do not reflect species hypotheses. For instance, what is regarded as a single species can be associated with two distinct DNA barcodes, which can point either to cryptic diversity or to within‐species mitochondrial divergences without reproductive isolation. In contrast, two or more species can share barcodes, for instance due to mitochondrial introgression. These intrinsic limitations of DNA barcoding are commonly addressed with nuclear genomic markers, which are expensive, may have low repeatability and often require high‐quality DNA. To overcome these limitations, we examined the use of ultraconserved elements (UCEs) as a quick and robust genomic approach to address such problematic cases of species delimitation in bees. This genomic method was assessed using six different species complexes suspected to harbour cryptic diversity, mitochondrial introgression or mitochondrial paraphyly. The sequencing of UCEs recovered between 686 and 1,860 homologous nuclear loci and provided explicit species delimitation in all investigated species complexes. These results provide strong evidence for the suitability of UCEs as a fast method for species delimitation even in recently diverged lineages. Furthermore, we provide the first evidence for both mitochondrial introgression among distinct bee species, and mitochondrial paraphyly within a single bee species.

Phylogeography and population genomics of a lotic water beetle across a complex tropical landscape - Athena Wai Lam; Morgan Gueuning; Carolin Kindler; Matthew Van Dam; Nadir Alvarez; Rawati Panjaitan; Helena Shaverdo; Lloyd T. White; George K. Roderick; Michael Balke (Molecular Ecology, 2018)
The habitat template concept applied to a freshwater system indicates that lotic species, or those which occupy permanent habitats along stream courses, are less dispersive than lentic species, or those that occur in more ephemeral aquatic habitats. Thus, populations of lotic species will be more structured than those of lentic species. Stream courses include both flowing water and small, stagnant microhabitats that can provide refuge when streams are low. Many species occur in these microhabitats but remain poorly studied. Here, we present population genetic data for one such species, the tropical diving beetle Exocelina manokwariensis (Dytiscidae), sampled from six localities along a ~300 km transect across the Birds Head Peninsula of New Guinea. Molecular data from both mitochondrial (CO1 sequences) and nuclear (ddRAD loci) regions document fine‐scale population structure across populations that are ~45 km apart. Our results are concordant with previous phylogenetic and macroecological studies that applied the habitat template concept to aquatic systems. This study also illustrates that these diverse but mostly overlooked microhabitats are promising study systems in freshwater ecology and evolutionary biology. With the advent of next‐generation sequencing, fine‐scale population genomic studies are feasible for small nonmodel organisms to help illuminate the effect of habitat stability on species’ natural history, population structure and geographic distribution.